Stellar photon correlation detection with the Southern Connecticut stellar interferometer - Weiss, Samuel A.; Rupert, Justin D.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a portable optical intensity interferometer located on the campus of Southern Connecticut State University in New Haven, Connecticut. Since its completion in 2016, the instrument has been used to take engineering data of bright stars. This paper will discuss the data collection and analysis methods, as well as the progress toward reliably measuring a significant stellar photon correlation. Vega has been the main star chosen for test observations to date because its diameter is well known by other methods, and it is not an extended source for the baselines used. The correlation peak in the processed data is compared to theoretical expectations. Given our expected sensitivity, a significant correlation peak is expected for small baselines (~2 m) to appear after a few hours of observation. So far, the observations indicate that the correlation peak is at the expected time delay, and the signal-to-noise ratio roughly scales as predicted.
Keywords: Avalanche diodes; Correlation peaks; Engineering data; Extended sources; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Optical intensities; Particle beams; Photon correlation; Photons; Quantum optics; Signal to noise ratio; Single photon avalanche diode; Stars; Stellar interferometers; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation